Systematic Literature Review on the Intersection of Financial Literacy, Financial Digitalization, and SMEs : A Comprehensive Analysis - Moch. Wahyu Widodo (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2025)
The main objective of this study is to present a comprehensive perspective on the interrelationship and impact of financial literacy, financial digitalization, and Small and Medium Enterprises (SMEs) on the growth and adaptability of SMEs in today's dynamic business landscape. This research uses a systematic literature observation method to collect, analyze and synthesize relevant findings from various published literature sources, especially selections in the Scopus database. The primary focus of this study is to examine the correlation between financial literacy and financial digitalization, and how they impact SMEs' financial management capabilities and utilization of available financial technology. The findings show that financial literacy and financial digitalization are important areas of study that have received increasing attention in recent years. This research highlights the challenges in accessing finance and reducing collateral demands, indicating the struggles that SMEs are currently facing.